Makna Sosial Budaya Dari Peta Distribusi Maleo Dalam Perspektif Konservasi Berbasis Komunitas - Daud Yusuf; Zuliyanto Zakaria; Ahmad Fauzi C Diko (Badan Riset dan Inovasi Nasional (BRIN), 2025)
The maleo bird (Macrocephalon maleo) is an endemic species of Sulawesi that holds both ecological and symbolic value for local communities. The distribution of the maleo is not only determined by ecological factors such as habitat availability, environmental suitability for nesting, climate change, and predator threats, but is also closely related to the socio-cultural dynamics of the surrounding communities. This article discusses the socio-cultural meaning of the maleo distribution map with an emphasis on a community-based conservation perspective. Through geospatial data and the exploration of local wisdom practices, it is evident that maleo distribution areas often intersect with the social spaces of indigenous communities, settlements, and symbols of collective identity. The presence of the maleo is regarded as part of cultural heritage passed down through generations, giving rise to traditional protection practices, such as restrictions on excessive egg collection or the designation of customary areas as conservation zones. The community-based perspective shows that conservation is not only focused on species preservation but also on strengthening the role of local communities as key actors. By integrating ecological distribution and socio-cultural values, maleo conservation efforts are expected to be more effective, adaptive, and sustainable. This article emphasizes that the success of maleo conservation largely depends on the recognition of the cultural values attached to its distribution as well as the active participation of communities in Sulawesi.